Determination of the Nucleotide Sequence of a Thermostable Xylanase Gene from Bacillus Coagulans ST-6 - M. S. Suhaimi, Ainu Husna (1999)
PBNXI is a recombinant plasmid containing vector plasmid pUC19 and a 2.6 kb fragment of Bacillus coagulans ST-6 genomic DNA which contains a xylanase gene. PBNX2 is another recombinant plasmid with the same insert DNA but in a pUC 18 vector. Both plasmids expressed xylanase activity when grown on RBB-Xylan agar plates. Preliminary to nucleotide sequencing, the recombinant plasmids were modified using restriction enzyme deletion to remove a segment of the insert DNA. The original insert DNA which was 2.6 kb was successfully reduced to a 0.8 kb and a 1.8 kb fragment in pBNXIA and pBNX2A respectively. The deletion was done using restriction endonuclease Sail and the resulting deletion mutants together with the original clones were used to determine the nucleotide sequence of the xylanase gene. By primer walking, 1420 bp of the forward sequence was obtained where an open reading frame (ORF) was found at 544 bp of the insert DNA. This 630 bp frame was preceeded by the putative E.coli - 10 and -35 promoters. No sequence corresponding to the signal peptide was found in this sequence. The open reading frame (ORF) was translated into a peptide of 2 1 0 amino acid residues. This protein belonged to Family G 11 of the Glycosyl Hydrolase family and had 59% homology with Bacillus stearothermophilus xylanase and 54% homology with xylanase from Aeromonas caviae. Eleven out of 20 completely conserved amino acids in this family were also conserved in this sequence and two conserved glutamate residues, E 104 and E 186 were directly involved in the enzyme's acid-catalytic mechanism. Secondary structure prediction showed that this enzyme consisted of two a-helices and 10 B-strands. Phylogenic studies showed that the primary structure of the enzyme was most closely related to Bacillus pumilus xylanase's primary structure. The analysis of the deduced amino acid sequence showed that there were five cysteine residues in this sequence compared to none in four other mesophilic xylanases. These cysteine residues can form internal disulfide bonds among themselves which can increase the stability of the protein. Analyzing the predicted secondary structure, an extra a-helical structure which is a more stable secondary structure was observed in comparison to other mesophilic xylanases. These two factors namely the presence of cysteine residues and the extra a-helical structure may have an important role in determining the thermo stability of this enzyme.